1986
DOI: 10.1042/bj2350421
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biosynthesis of complement component C3 and α-1 acid glycoprotein by adult rat hepatocytes in a co-culture system with an epithelial liver cell-type

Abstract: We used a system of co-culture of adult rat hepatocytes with another epithelial cell type from rat liver to study the synthesis of two acute-phase reactants, alpha-1 acid glycoprotein (alpha 1AGP) and the third component of complement (C3), and we have obtained long-term secretion of these two proteins. After a period of adaptation corresponding to the first 2-4 days of the co-culture, hepatocytes secreted C3 and alpha 1AGP for at least 2 weeks at a mean level higher than that observed in the first days of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It was reported that hepatocytes were cocultured with non-parenchymal cells of liver and this coculture system succeeded in the maintenance of liver functions for a long term. [23][24][25] The coculture system in the present study seems available for investigation of lipid transport from hepatocytes to muscle cells, probably also for other studies on cellular interaction between these cells.…”
Section: C-secreted Lipoprotein In the Medium With Lplmentioning
confidence: 99%
“…It was reported that hepatocytes were cocultured with non-parenchymal cells of liver and this coculture system succeeded in the maintenance of liver functions for a long term. [23][24][25] The coculture system in the present study seems available for investigation of lipid transport from hepatocytes to muscle cells, probably also for other studies on cellular interaction between these cells.…”
Section: C-secreted Lipoprotein In the Medium With Lplmentioning
confidence: 99%
“…This unfavorable situation is considerably improved if the hepatocytes are co-cultured with liver epithelial cell lines (Guguen- Guillouzo and Guillouzo, 1983;GuguenGuillouzo et al, 1983;Begue et al, 1984;Wegner et al, 1990). Co-cultivation not only prolonged the lifespan of the cultured hepatocytes, but also maintained their functional capacity and enhanced their response to various inducing agents (Clement et al, 1984;Lebreton et al, 1986;Foliot et al, 1985;Vandenberghe et al, 1988;Schrode et al, 1990;Wegner et al, 1990). There is increasing evidence that co-cultures are better suited for studies on the metabolism of xenobiotics than pure cultures of rat hepatocytes (Rogiers et al, 1990;Donato et al, 1991;Niemann et al, 1991;Akrawi et al, 1993;Coecke et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable step forward in long-term maintenance of differentiated hepatocytes was made by adding another liver epithelial cell type (126). When cocultured with rat liver epithelial cells probably derived from primitive biliary cells, hepatocytes from various species including humans survive for several weeks and retain various liverspecific functions; these include production of plasma proteins, expression of both phase I and phase II drug metabolizing enzymes, and taurocholate uptake (52,71,(127)(128)(129)(130)(131)(132)(133)(134)(135) (71,126,128) and with preservation of communication through gap junctions (136). These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%